A high-tenacity polybutylene terephthalate material and a method of making the same

CN122628511BActive Publication Date: 2026-10-09JIANGSU KEYILAI NEW MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611070985.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-09
Estimated Expiration
2046-07-20

AI Technical Summary

Technical Problem

该发明将分子量高、支化程度高的支化聚苯乙烯与PET通过熔融共混制备出加工性能良好的高韧性PET,制备方法简单易行,但其冲击强度仍有待提高

Benefits of technology

[0022]The high-toughness polybutylene terephthalate material prepared by this invention has excellent tensile strength, elongation at break and notched impact strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122628511B_ABST
    Figure CN122628511B_ABST
Patent Text Reader

Abstract

The application discloses a high-toughness polybutylene terephthalate material and a preparation method thereof, and relates to the technical field of polybutylene terephthalate. The high-toughness polybutylene terephthalate material comprises the following raw materials in parts by weight: PBT resin 70-80 parts, a reactive toughening agent 12-15 parts, maleic anhydride grafted polyolefin 4-6 parts, modified montmorillonite 2-3 parts, an antioxidant 0.5-0.8 parts, a lubricant 0.3-0.5 parts, and an anti-hydrolysis agent 0.5-1.2 parts. The high-toughness polybutylene terephthalate material prepared by the application has excellent tensile strength, elongation at break, notched impact strength and heat distortion temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polybutylene terephthalate (PET) technology, specifically to a high-toughness PET material and its preparation method. Background Technology

[0002] Polybutylene terephthalate (PBT) is an aromatic polyester with excellent mechanical properties, electrical properties, heat resistance, chemical resistance, and dimensional stability, making it widely used in the automotive, electronics, and electrical appliance industries. However, the benzene ring and ester groups in the PBT molecular chain form a rigid conjugated structure, resulting in insufficient molecular chain flexibility. This leads to low notched impact strength and poor toughness, limiting its application in high-stress impact environments. To improve the toughness of PBT materials, elastomers are commonly used for toughening modification. While this can improve impact strength to some extent, the significant polarity difference between elastomers and PBT leads to insufficient compatibility and a tendency for interfacial debonding, thus affecting its mechanical properties. Furthermore, high elastomer content can decrease the tensile strength, flexural modulus, and dimensional stability of PBT materials, making it difficult to achieve a balance between toughness and rigidity.

[0003] Chinese invention patent CN105524433A discloses a method for preparing high-toughness PET. This method involves adding an appropriate amount of branched polystyrene (BPS) to a PET matrix and then melt-blending it to obtain a PET / BPS blend. The amount of BPS is 0.5%-2.0% of the weight of the PET. Compared with pure PET, this PET / BPS blend exhibits a 10%-20% increase in impact strength and a 50%-400% elongation at break, demonstrating a significant improvement in toughness. This invention prepares high-toughness PET with good processing performance through melt blending of high-molecular-weight, highly branched polystyrene with PET. The preparation method is simple and easy to implement, but its impact strength still needs improvement. Summary of the Invention

[0004] To address the shortcomings of existing technologies, the purpose of this invention is to provide a high-toughness polybutylene terephthalate material and its preparation method.

[0005] A high-toughness polybutylene terephthalate material, comprising the following raw materials by weight:

[0006] 70-80 parts PBT resin, 12-15 parts reactive toughening agent, 4-6 parts maleic anhydride grafted polyolefin, 2-3 parts modified montmorillonite, 0.5-0.8 parts antioxidant, 0.3-0.5 parts lubricant, and 0.5-1.2 parts anti-hydrolysis agent;

[0007] The reactive toughening agent is prepared by the following method:

[0008] A polymer is obtained by polymerizing bihydroxypropyl silicone oil, polycaprolactone diol, POSS and isophorone diisocyanate under the action of a catalyst, and then the polymer is obtained by end-capping with glycidyl ether to obtain a reactive toughening agent.

[0009] The modified montmorillonite was prepared by the following method: sodium montmorillonite was dispersed in deionized water to obtain a dispersion; the pH of the laurylamidopropyl betaine aqueous solution was adjusted with hydrochloric acid solution and then added to the dispersion to obtain the modified montmorillonite through an ion exchange reaction.

[0010] The mass ratio of the dual-terminated hydroxypropyl silicone oil, polycaprolactone diol, POSS, isophorone diisocyanate and glycidyl is 100:(10-20):(1-3):(30-38):(10-15).

[0011] The catalyst is dibutyltin dilaurate.

[0012] The POSS is 1,2-propanediol isobutyl POSS.

[0013] The antioxidant is one of antioxidant 1010 and antioxidant 168.

[0014] The lubricant is one of ethylene bis-stearamide and calcium stearate.

[0015] The anti-hydrolysis agent is carbodiimide.

[0016] The pH value is 4.

[0017] The mass ratio of sodium montmorillonite to lauramide propyl betaine is 1:0.35.

[0018] A method for preparing a high-toughness polybutylene terephthalate material includes the following steps:

[0019] (1) Weigh out the following by weight: 70-80 parts of PBT resin, 12-15 parts of reactive toughening agent, 4-6 parts of maleic anhydride grafted polyolefin, 2-3 parts of modified montmorillonite, 0.5-0.8 parts of antioxidant, 0.3-0.5 parts of lubricant, and 0.5-1.2 parts of anti-hydrolysis agent;

[0020] (2) PBT resin, reactive toughening agent, maleic anhydride grafted polyolefin, modified montmorillonite, antioxidant, lubricant and anti-hydrolysis agent are mixed evenly to obtain a mixture; the mixture is melt-blended, extruded, cooled and pelletized using an extruder to obtain high-toughness polybutylene terephthalate material.

[0021] Due to the adoption of the above technical solutions, the beneficial effects of the present invention include:

[0022] The high-toughness polybutylene terephthalate material prepared by this invention has excellent tensile strength, elongation at break and notched impact strength. Attached Figure Description

[0023] Figure 1 Fourier transform infrared spectrum of the reactive toughening agent prepared in Example 1.

[0024] Figure 2 The 1H NMR spectrum of the reactive toughening agent prepared in Example 1.

[0025] Figure 3 Fourier transform infrared spectra of sodium-based montmorillonite and modified montmorillonite prepared in Example 4.

[0026] Figure 4 X-ray diffraction patterns of sodium-based montmorillonite and modified montmorillonite prepared in Example 4. Detailed Implementation

[0027] Example 1: Preparation of reactive toughening agent

[0028] Under nitrogen protection, 100g of hydroxypropyl dimethyl silicone oil, 10g of polycaprolactone diol, 1g of 1,2-propanediol isobutyl POSS, 30g of isophorone diisocyanate and 0.05g of dibutyltin dilaurate were added to a reaction flask, stirred and mixed, heated to 75℃ and reacted for 6h. The temperature was then lowered to 55℃, and 10g of glycidyl ether was slowly added dropwise over 20min. The reaction was maintained at this temperature for 3h, and then distilled under reduced pressure at -0.08MPa for 1h. After cooling to room temperature, the reactive toughening agent was obtained.

[0029] Figure 1 The Fourier transform infrared spectrum of the reactive toughening agent is shown in the figure. It can be seen from the figure that at 3340 cm⁻¹... -1 A broad absorption peak appears nearby, which is the stretching vibration peak of NH; 2920 cm⁻¹ -1 and 2850cm -1 The nearby absorption peak is the stretching vibration peak of aliphatic -CH2-; 1720 cm⁻¹ -1 The peak appearing nearby is the C=O stretching vibration peak of carbamate; 1530 cm⁻¹ -1 The nearby peaks are absorption peaks of NH bending and CN stretching vibrations; 1260 cm⁻¹ -1 The absorption peak appearing nearby is a Si-CH3 vibrational peak; 1050 cm⁻¹ -1 The absorption peak appearing nearby is the Si-O-Si stretching vibration peak, 910 cm⁻¹. -1 The peaks appearing nearby are characteristic absorption peaks of epoxy groups. The appearance of these characteristic peaks indicates that the reactive toughening agent has been successfully prepared.

[0030] Figure 2The figure shows the 1H NMR spectrum (CDCl3, 400MHz) of the reactive toughening agent. As can be seen from the figure, the broad peak at δ 4.80-5.20ppm represents the NH protons in the urethane structure; the multiplet at δ 3.10-4.15ppm represents the -O-CH2- protons; the peaks at δ 2.55-2.90ppm and δ 2.10-2.50ppm correspond to the epoxy methine and epoxy methylene proton peaks, respectively; the multiplet at δ 1.05-1.95ppm represents the methylene and methine protons in the polycaprolactone segment, the IPDI alicyclic structure, and the propyl segment; the peak at δ 0.85-1.05ppm represents the methyl protons in the isobutyl side chain of POSS; and the peak at δ 0.5-0.7ppm represents the -Si-CH2- protons. The strong absorption signal appearing at -0.3 to 0.3 ppm is due to the Si-CH3 protons in the polydimethylsiloxane chain. The above results indicate that the glycidyl-terminated siloxane-polyurethane reactive toughening agent was successfully prepared.

[0031] Example 2 Preparation of reactive toughening agent

[0032] Under nitrogen protection, 100g of hydroxypropyl dimethyl silicone oil, 15g of polycaprolactone diol, 2g of 1,2-propanediol isobutyl POSS, 35g of isophorone diisocyanate and 0.06g of dibutyltin dilaurate were added to a reaction flask, stirred and mixed, heated to 80℃ and reacted for 5h. The temperature was then lowered to 60℃, and 12g of glycidyl was slowly added dropwise over 20min. The reaction was maintained at this temperature for 2.5h, and then distilled under reduced pressure at -0.08MPa for 1h. After cooling to room temperature, the reactive toughening agent was obtained.

[0033] Example 3 Preparation of reactive toughening agent

[0034] Under nitrogen protection, 100g of hydroxypropyl dimethyl silicone oil, 20g of polycaprolactone diol, 3g of 1,2-propanediol isobutyl POSS, 38g of isophorone diisocyanate and 0.08g of dibutyltin dilaurate were added to a reaction flask, stirred and mixed, heated to 85℃ and reacted for 4h, then cooled to 65℃, and 15g of glycidyl was slowly added dropwise over 20min. The reaction was maintained at this temperature for 2h, and then distilled under reduced pressure at -0.08MPa for 1h. After cooling to room temperature, a reactive toughening agent was obtained.

[0035] Example 4 Preparation of modified montmorillonite

[0036] Mix 300 ml of deionized water and 10 g of sodium montmorillonite, and ultrasonically disperse at 30 kHz and 200 W for 20 min. Heat to 70 °C and stir for 2 h to obtain a dispersion. Separately, take 10 g of 35 wt% lauramidopropyl betaine aqueous solution, adjust the pH to 4 with 0.1 mol / L hydrochloric acid solution, and slowly add it to the dispersion. Stir at 70 °C for 4 h, maintaining the pH at 4 with 0.1 mol / L hydrochloric acid solution during the process (pH fluctuation range not exceeding ±0.2). Let stand for 1 h to age, cool to room temperature, filter, and wash the filter cake with deionized water until neutral, wash with 50 ml of anhydrous ethanol, vacuum dry at 80 °C for 12 h, pulverize, and pass through a 200 mesh sieve to obtain modified montmorillonite.

[0037] Figure 3 The figures show the Fourier transform infrared spectra of sodium-based montmorillonite and modified montmorillonite. As can be seen from the figures, at 3620 cm⁻¹... -1 The absorption peak appearing nearby is the absorption peak of the stretching vibration of the hydroxyl group Al-OH; at 3440 cm⁻¹ -1 The relatively broad absorption peak nearby is due to the OH stretching vibration absorption peak of adsorbed water or interlayer water; 1635 cm⁻¹ -1 The nearby peak is a HOH bending vibration peak; 1040 cm⁻¹ -1 The absorption peak appearing nearby is the Si-O-Si stretching vibration peak, 840 cm⁻¹. -1 The nearby peak is an Al-Mg-OH bending vibration peak; 520 cm⁻¹ -1 and 470cm -1 The nearby absorption peaks are Si-O-Al and Si-O-Si bending vibration peaks, respectively. Modified montmorillonite retains the relevant absorption peaks of sodium-based montmorillonite, and also shows a peak at 2920 cm⁻¹. -1 and 2850cm -1 A long-chain alkyl -CH2- stretching vibration peak appears nearby, at 1540-1550 cm⁻¹. -1 The absorption peaks appearing nearby are coupling absorption peaks of the NH bending vibration and CN stretching vibration; in the 1450-1470 cm⁻¹ range... -1 The presence of an absorption peak nearby indicates a -CH2- bending vibration peak, and these characteristic peaks prove that the modified montmorillonite was successfully prepared.

[0038] Figure 4The X-ray diffraction patterns of sodium-based montmorillonite and modified montmorillonite are shown in the figure. As can be seen from the figure, sodium-based montmorillonite exhibits a distinct (001) crystal plane diffraction peak at 2θ = 7.1°, corresponding to an interlayer spacing of 1.24 nm. After modification with laurylamidopropyl betaine, the (001) crystal plane diffraction peak of modified montmorillonite shifts to 2θ = 5.1°, and the interlayer spacing increases to 1.71 nm, indicating that laurylamidopropyl betaine enters the interlayer of montmorillonite and expands the interlayer spacing. Modified montmorillonite still retains the characteristic diffraction peaks of layered silicates, indicating that the basic layered structure of montmorillonite was not destroyed after modification.

[0039] Example 5 Preparation of high-toughness polybutylene terephthalate material

[0040] (1) Weigh out: 700g of PBT resin, 120g of reactive toughening agent (prepared in Example 1), 40g of maleic anhydride-grafted polyolefin (maleic anhydride-grafted POE), 20g of modified montmorillonite (prepared in Example 4), 5g of antioxidant (antioxidant 1010), 3g of lubricant (ethylene bis-stearamide), and 5g of anti-hydrolysis agent (carbodiimide);

[0041] (2) PBT resin, reactive toughening agent, maleic anhydride grafted polyolefin, modified montmorillonite, antioxidant, lubricant and anti-hydrolysis agent are mixed and stirred at 500 rpm for 20 min. The mixture is then added to a twin-screw extruder with a screw speed of 250 r / min, a feeding section temperature of 180℃, a melting section temperature of 220℃, a mixing section temperature of 235℃ and an extrusion section temperature of 240℃. The mixture is cooled to room temperature in a water bath, pelletized, and vacuum dried at 110℃ for 4 h to obtain high-toughness polybutylene terephthalate material.

[0042] Example 6 Preparation of high-toughness polybutylene terephthalate material

[0043] (1) Weigh out: 750g of PBT resin, 140g of reactive toughening agent (prepared in Example 2), 50g of maleic anhydride-grafted polyolefin (maleic anhydride-grafted POE), 25g of modified montmorillonite (prepared in Example 4), 6g of antioxidant (antioxidant 1010), 4g of lubricant (ethylene bis-stearamide), and 10g of anti-hydrolysis agent (carbodiimide);

[0044] (2) PBT resin, reactive toughening agent, maleic anhydride grafted polyolefin, modified montmorillonite, antioxidant, lubricant and anti-hydrolysis agent are mixed and stirred at 500 rpm for 20 min. The mixture is then added to a twin-screw extruder with a screw speed of 150 r / min, a feeding section temperature of 180℃, a melting section temperature of 220℃, a mixing section temperature of 235℃ and an extrusion section temperature of 240℃. The mixture is cooled to room temperature in a water bath, pelletized, and vacuum dried at 110℃ for 4 h to obtain high-toughness polybutylene terephthalate material.

[0045] Example 7 Preparation of high-toughness polybutylene terephthalate material

[0046] (1) Weigh out: 800g of PBT resin, 150g of reactive toughening agent (prepared in Example 3), 60g of maleic anhydride-grafted polyolefin (maleic anhydride-grafted POE), 30g of modified montmorillonite (prepared in Example 4), 8g of antioxidant (antioxidant 168), 5g of lubricant (calcium stearate), and 12g of anti-hydrolysis agent (carbodiimide);

[0047] (2) PBT resin, reactive toughening agent, maleic anhydride grafted polyolefin, modified montmorillonite, antioxidant, lubricant and anti-hydrolysis agent are mixed and stirred at 500 rpm for 20 min. The mixture is then added to a twin-screw extruder with a screw speed of 150 r / min, a feeding section temperature of 180℃, a melting section temperature of 220℃, a mixing section temperature of 235℃ and an extrusion section temperature of 240℃. The mixture is cooled to room temperature in a water bath, pelletized, and vacuum dried at 110℃ for 4 h to obtain high-toughness polybutylene terephthalate material.

[0048] Comparative Example 1

[0049] The preparation method of the high-toughness polybutylene terephthalate material is basically the same as that in Example 6, except that the reactive toughening agent is replaced with an equal weight of a reactive toughening agent prepared by the following method:

[0050] The preparation method of the reactive toughening agent is basically the same as that in Example 2, except that isophorone diisocyanate is replaced with 15.1g of hexamethylene diisocyanate.

[0051] Comparative Example 2

[0052] The preparation method of the high-toughness polybutylene terephthalate material is basically the same as that in Example 6, except that the reactive toughening agent is replaced with an equal weight of a reactive toughening agent prepared by the following method:

[0053] The preparation method of the reactive toughening agent is basically the same as that in Example 2, except that isophorone diisocyanate is replaced with 15.7g of 2,4-toluene diisocyanate.

[0054] Comparative Example 3

[0055] The preparation method of the high-toughness polybutylene terephthalate material is basically the same as that in Example 6, except that the reactive toughening agent is replaced with an equal weight of a reactive toughening agent prepared by the following method:

[0056] The preparation method of the reactive toughening agent is basically the same as that in Example 2, except that the amount of 1,2-propanediol isobutyl POSS added is replaced with 5g.

[0057] Comparative Example 4

[0058] The preparation method of the high-toughness polybutylene terephthalate material is basically the same as that in Example 6, except that the reactive toughening agent is replaced with an equal weight of a reactive toughening agent prepared by the following method:

[0059] The preparation method of the reactive toughening agent is basically the same as that in Example 2, except that the amount of polycaprolactone diol added is replaced with 25g.

[0060] Comparative Example 5

[0061] The preparation method of the high-toughness polybutylene terephthalate material is basically the same as that in Example 6, except that the modified montmorillonite is replaced with an equal weight of sodium-based montmorillonite.

[0062] Comparative Example 6

[0063] The preparation method of the high-toughness polybutylene terephthalate material is basically the same as that in Example 6, except that the modified montmorillonite is replaced with an equal weight of modified montmorillonite prepared by the following method:

[0064] The preparation method of modified montmorillonite is basically the same as that in Example 4, except that lauramide propyl betaine is replaced with an equal weight of hexadecyltrimethylammonium bromide.

[0065] Comparative Example 7

[0066] The preparation method of the high-toughness polybutylene terephthalate material is basically the same as that in Example 6, except that the modified montmorillonite is replaced with an equal weight of modified montmorillonite prepared by the following method:

[0067] The preparation method of modified montmorillonite is basically the same as that in Example 4, except that lauramide propyl betaine is replaced with an equal weight of decyl betaine (CAS: 2644-45-3).

[0068] Comparative Example 8

[0069] The preparation method of the high-toughness polybutylene terephthalate material is basically the same as that in Example 6, except that the modified montmorillonite is replaced with an equal weight of modified montmorillonite prepared by the following method:

[0070] The preparation method of modified montmorillonite is basically the same as that in Example 4, except that the pH is adjusted to 5.

[0071] The PBT resin used in the embodiments and comparative examples of this application is model K095, manufactured by Jiangsu Keyila New Material Technology Co., Ltd.; the double-ended hydroxypropyl silicone oil is model IOTA 2030-10, with a hydroxyl content of 2.5%, manufactured by Anhui Aiyota Silicone Oil Co., Ltd.; the maleic anhydride-grafted POE is model CMG5904, manufactured by Jiayirong Polymer (Shanghai) Co., Ltd.; the polycaprolactone diol has a number average molecular weight of 1000; and the sodium montmorillonite is model PGW, with a specific surface area of ​​700 m². 2 / g. All the above materials were dried at 110℃ for 5h before use; the CAS number of 1,2-propanediol isobutyl POSS is 480439-49-4.

[0072] The high-toughness polybutylene terephthalate materials prepared in the examples and comparative examples were tested for crystallization temperature, tensile strength, elongation at break, notched impact strength and heat distortion temperature. The test results are shown in Table 1.

[0073] Crystallization temperature test: The crystallization peak temperature was tested according to GB / T 19466.3-2004 standard.

[0074] Sample preparation: The high-toughness polybutylene terephthalate material prepared in the examples and comparative examples was placed in a mold (different test methods use different sized molds), preheated at 250℃ for 5 min; after venting, it was held under pressure of 10 MPa for 5 min, cooled to room temperature by circulating water at 25℃, demolded, and allowed to stand at room temperature for 24 h. It was then conditioned for 24 h in a standard environment of 23℃ and 50% relative humidity to obtain the test sample.

[0075] Tensile strength and elongation at break tests: Tested according to GB / T 1040.2-2022 standard. The specimen is a type 1A dumbbell shape. The test is conducted using an electronic universal testing machine with a tensile speed of 50 mm / min.

[0076] Notched impact strength test: Tested according to GB / T 1843-2008 standard, the sample size is 80mm×10mm×4mm, and the notch type is type A notch.

[0077] Heat distortion temperature test: Tested according to GB / T 1634.2-2019 standard, the sample size is 80mm×10mm×4mm, and the applied bending stress is 0.45MPa.

[0078] Table 1 Performance Test Data

[0079]

[0080] As can be seen from the data in Table 1, the high-toughness polybutylene terephthalate material prepared by the present invention has excellent tensile strength, elongation at break, notched impact strength and heat distortion temperature. This is because the reactive toughening agent, maleic anhydride-grafted polyolefin, modified montmorillonite and other additives form a synergistic toughening and strengthening effect in the PBT matrix.

[0081] The high-toughness polybutylene terephthalate (PPT) material prepared by this invention uses PBT resin as the main component, enabling the material to maintain good tensile strength and molding stability. The prepared reactive toughening agent contains polysiloxane flexible segments, polycaprolactone segments, POSS cage structure, urethane groups, and terminal epoxy groups. Among them, the terminal epoxy groups can undergo ring-opening reactions with the terminal carboxyl and hydroxyl groups of PBT molecular chains during melt processing, enhancing the interfacial bonding force between the toughening agent and the PBT matrix, which is beneficial to stress transfer; the flexible polysiloxane segments can improve the system's flexibility and impact energy absorption capacity; the polycaprolactone segments have good structural compatibility with the PBT matrix, which is beneficial to the uniform dispersion of the toughening agent in PBT; the rigid POSS cage structure can compensate for the decrease in rigidity and heat resistance caused by the addition of flexible toughening agents, so that the material maintains high tensile strength and heat resistance; the highly polar urethane groups can form hydrogen bonds or dipole interactions with the ester groups in the PBT molecular chains and the polar groups on the surface of modified montmorillonite, reducing the phase separation phenomenon of the toughening agent in the matrix. After montmorillonite is modified by lauramidopropyl betaine intercalation, the interaction forces between the lamellar layers are weakened, which facilitates the entry of polymer (such as PBT, maleic anhydride-grafted polyolefin) molecular chains into the interlayer under melt shear, promoting the dispersion of montmorillonite lamellar layers. The lamellar structure enables the material to induce crack deflection and passivation under stress, prolonging the crack propagation path and improving the material's strength. Furthermore, lamellar montmorillonite can act as a heterogeneous nucleating agent, lowering the nucleation energy barrier required for PBT molecular chain crystallization and increasing the crystallization temperature. In addition, lubricants can improve processing fluidity and promote dispersion; antioxidants can inhibit the thermo-oxidative degradation of PBT and organic components during melt processing, improving processing stability and thermo-oxidative stability. The synergistic effect of these components yields a butyl terephthalate material with excellent tensile strength, elongation at break, notched impact strength, heat distortion temperature, and crystallization temperature.

[0082] Comparative Example 1 uses a reactive toughening agent with hexamethylene diisocyanate, which exhibits strong molecular chain flexibility but relatively reduced interfacial support. This makes it difficult to form a transitional structure with both flexible energy dissipation and strong interfacial bonding between the PBT matrix and the polysiloxane segments, resulting in a decrease in the material's tensile strength, notched impact strength, and heat distortion temperature. Comparative Example 2 uses a reactive toughening agent with 2,4-toluene diisocyanate, which is highly rigid but lacks flexibility, easily forming locally hard micro-regions. This reduces the material's ability to uniformly transfer stress and dissipate energy during impact, thus lowering its elongation at break and notched impact strength. Comparative Example 3 uses a reactive toughening agent with increased POSS content, resulting in an excessively rigid cage-like structure. This forms locally hard micro-regions in the matrix, causing stress concentration and reducing the toughening agent's flexibility, elongation at break, and notched impact strength. Comparative Example 4 uses a reactive toughening agent with increased polycaprolactone segment content, reducing the system's rigidity and thermal stability. It also reduces the contribution of POSS and terminal epoxy reactive groups, leading to a decrease in tensile strength, notched impact strength, and heat resistance.

[0083] In Comparative Example 5, unmodified sodium-based montmorillonite was used. Due to its strong hydrophilicity and poor compatibility with PBT, the montmorillonite agglomerated in the matrix, failing to fully exert its lamellar reinforcement and crack-resistant effects, resulting in reduced performance. Comparative Example 6 used CTAB-modified montmorillonite, which lacked amide groups and zwitterionic structures. Its interfacial interactions with PBT and reactive toughening agents were weaker than those with laurylamidopropyl betaine, leading to reduced performance. In Comparative Example 7, decyl betaine was used for intercalation of montmorillonite. The lack of hydrogen bonds and dipole interactions from the amide groups resulted in a lower degree of organication of the montmorillonite interlayers, leading to decreased material performance. In Comparative Example 8, adjusting the pH to 5 reduced the protonation degree of laurylamidopropyl betaine, weakening its exchange adsorption with the montmorillonite interlayers. This resulted in a slight decrease in the degree of organic modification, interlayer spacing, and dispersion stability, thus reducing the material's mechanical and thermal stability.

[0084] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. However, any modifications, alterations, and variations made by those skilled in the art without departing from the scope of the present invention based on the disclosed technical content are equivalent embodiments of the present invention. Furthermore, any modifications, alterations, and variations made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the present invention.

Claims

1. A high-toughness polybutylene terephthalate material, characterized in that, Raw materials comprising the following weight components: 70-80 parts PBT resin, 12-15 parts reactive toughening agent, 4-6 parts maleic anhydride grafted polyolefin, 2-3 parts modified montmorillonite, 0.5-0.8 parts antioxidant, 0.3-0.5 parts lubricant, and 0.5-1.2 parts anti-hydrolysis agent; The reactive toughening agent is prepared by the following method: A polymer is obtained by polymerization of hydroxypropyl silicone oil, polycaprolactone diol, POSS and isophorone diisocyanate under the action of a catalyst, and then a reactive toughening agent is obtained by end-capping with glycidyl ester. The modified montmorillonite was prepared by the following method: Sodium montmorillonite was dispersed in deionized water to obtain a dispersion. The solution of lauramidopropyl betaine was prepared by adjusting the pH of the aqueous solution with hydrochloric acid and then adding it to the dispersion via an ion exchange reaction. The mass ratio of the double-ended hydroxypropyl silicone oil, polycaprolactone diol, POSS, isophorone diisocyanate and glycidyl is 100:(10-20):(1-3):(30-38):(10-15); POSS is 1,2-propanediol isobutyl POSS. The pH is 4; the mass ratio of sodium montmorillonite to lauramide propyl betaine is 1:0.

35.

2. The high-toughness polybutylene terephthalate material according to claim 1, characterized in that, The catalyst is dibutyltin dilaurate.

3. The high-toughness polybutylene terephthalate material according to claim 1, characterized in that, The antioxidant is one of antioxidant 1010 and antioxidant 168.

4. The high-toughness polybutylene terephthalate material according to claim 1, characterized in that, The lubricant is one of ethylene bis-stearamide and calcium stearate.

5. The high-toughness polybutylene terephthalate material according to claim 1, characterized in that, The anti-hydrolysis agent is carbodiimide.

6. A method for preparing a high-toughness polybutylene terephthalate material as described in any one of claims 1-5, characterized in that, Includes the following steps: (1) Weigh out the following by weight: 70-80 parts of PBT resin, 12-15 parts of reactive toughening agent, 4-6 parts of maleic anhydride grafted polyolefin, 2-3 parts of modified montmorillonite, 0.5-0.8 parts of antioxidant, 0.3-0.5 parts of lubricant, and 0.5-1.2 parts of anti-hydrolysis agent; (2) PBT resin, reactive toughening agent, maleic anhydride grafted polyolefin, modified montmorillonite, antioxidant, lubricant and anti-hydrolysis agent are mixed evenly to obtain a mixture; the mixture is melt-blended, extruded, cooled and pelletized using an extruder to obtain high-toughness polybutylene terephthalate material.

Citation Information

Patent Citations

  • Method for preparing high-toughness PET (Polyethylene Terephthalate)

    CN105524433A

  • Toughened PBT (Polybutylene Terephthalate) engineering plastic and preparation method thereof

    CN102002215A

  • High-filling heat-conducting master batch applied to polyester plastics and preparation method of high-filling heat-conducting master batch

    CN115044192A

  • Preparation method of high-temperature-resistant halogen-free flame-retardant PC / PBT alloy material

    CN122255699A